Colon Trauma: Evidence-Based Practices - Yamamoto, Ryo; Logue, Alicia J.; Muir, Mark T. (Clinics in Colon and Rectal Surgery, 2018)
Colon injury is not uncommon and occurs in about a half of patients with penetrating hollow viscus injuries. Despite major advances in the operative management of penetrating colon wounds, there remains discussion regarding the appropriate treatment of destructive colon injuries, with a significant amount of scientific evidence supporting segmental resection with primary anastomosis in most patients without comorbidities or large transfusion requirement. Although literature is sparse concerning the management of blunt colon injuries, some studies have shown operative decision based on an algorithm originally defined for penetrating wounds should be considered in blunt colon injuries. The optimal management of colonic injuries in patients requiring damage control surgery (DCS) also remains controversial. Studies have recently reported that there is no increased risk compared with patients treated without DCS if fascial closure is completed on the first reoperation, or that a management algorithm for penetrating colon wounds is probably efficacious for colon injuries in the setting of DCS as well.
Keywords: nondestructive colon injury; destructive colon injury; blunt colon injury; damage control surgery; ostomy